Where Does Ascribed Privilege Get You in? Structural and Net Effects of Caste and Religious Belonging in India. (December 2022) - Ferry, Mathieu
Socio-economically advantaged upper castes tend to claim that Indian society is 'post-caste', suggesting that individuals from historically marginalized castes and religious groups do not face specific social barriers when attempting to move into white-collar positions. Alleged intergenerational mobility and the emergence of a 'new middle class' related to the growth of the private sector is widely used to counter affirmative action initiatives in higher education and public-sector recruitment. In this article, I test these claims by examining Brahmin, lower caste Dalit and Muslim patterns of intergenerational class and educational mobility of father–child pairs. I point to the strong role of caste and religion in shaping one's destination, particularly when accessing top occupational positions in the private sector. These results question the meritocratic and casteless claims of the Indian 'new middle class' in post-liberalization India, and they call for more encompassing policies reducing origin-based inequality.